.66x-4=-1

Simple and best practice solution for .66x-4=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .66x-4=-1 equation:


Simplifying
0.66x + -4 = -1

Reorder the terms:
-4 + 0.66x = -1

Solving
-4 + 0.66x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 0.66x = -1 + 4

Combine like terms: -4 + 4 = 0
0 + 0.66x = -1 + 4
0.66x = -1 + 4

Combine like terms: -1 + 4 = 3
0.66x = 3

Divide each side by '0.66'.
x = 4.545454545

Simplifying
x = 4.545454545

See similar equations:

| 6y+6=y-2 | | 1g(x+7)+1g(3x+1)=2 | | (-2)=4x+2 | | (x-3)*7=70 | | 0.05x=150 | | .66x-4=1 | | -4x+9x-(-4)=12x-5-(-10) | | 4y(5y-8)+24y= | | (x-10)*4=24 | | 2(4x-5)=12 | | x^2+2logX+94.3=0 | | (x+5)*6=54 | | (-3)=x^2-5 | | 3x-11+7x=51 | | x^2+lnX+92.3=0 | | n-(2n-1)=5-2(n-1) | | 12000(7+x)=108000 | | -12-5-6-(-25)= | | X-3.51=1.9 | | -25-7x=17 | | 4(x-f)=3(2w-x) | | 3*-10= | | 29-4x=5 | | 75=4(b+8.5) | | 896=x+2x | | 0.2cx=3a | | -24/-8= | | 6+2t=8 | | X-30=90 | | 3x(-1-2t)=4x(1-5t) | | cos(3x)=cos(0.5x) | | 3d+7=2d-17 |

Equations solver categories